PENGARUH DUKUNGAN ORANG TUA TERHADAP PRESTASI AKADEMIK SISWA - Salsabila, Syahla Rizkia; Marsofiyati; Utari, Eka Dewi (Yayasan Amanah Nur Aman, 2025)
This study looks at how parental support affects college students academic performance. Amidst the academic challenges and psychological pressures faced by students, parental involvement remains an important yet often overlooked factor. Using a quantitative approach with a survey method, data was collected from 43 students through a valid and reliable Likert scale questionnaire. The results indicate a moderate yet significant positive correlation (r = 0.419, p = 0.005) between parental support and academic performance. Additionally, regression analysis shows that parental support accounts for 17.5% of the variation in students' academic outcomes. These findings suggest that while academic performance is influenced by various factors, consistent emotional, financial, and motivational support from parents continues to play a meaningful role even at the higher education level. Strengthening parental involvement, particularly in emotional aspects, can be a strategic effort to enhance student achievement and well-being in higher education settings.